Standard for Organization Construction and Management of Rehabilitation Institutions - Working Group of Standard for Organization Construction and Management of Rehabilitation Institutions (康复学报)
National-level, provincial-level, prefectural-level, county-level rehabilitation centers and a large number of community-based rehabilitation institutions have been established in my country, basically forming a nationwide network of rehabilitation institutions. However, the development of rehabilitation institutions in China is greatly restricted due to the lack of standardized and unified industry management standards. To carry out research on the organization construction and management of rehabilitation institutions, to explore the management mode of rehabilitation institutions suitable for China's national conditions, and to standardize the construction and service standards of rehabilitation institutions are of great significance for guiding the development of various types of rehabilitation institutions at all levels in China. The guidelines adheres to the concept of "patient-centered", combined with the concept of CARF, focuses on the special requirements of rehabilitation, and mainly expounds from the aspects of standard application scope, organization construction standard, organization management standard, talent team allocation and rehabilitation service standard, so as to improve the standardization of organization construction and management of rehabilitation institutions and promote the development of rehabilitation medicine in China. Organization construction standards mainly include building construction standards, department construction standards, equipment configuration standards, etc; organization management standards mainly include leadership structure, formulation of strategies, collection of opinions and suggestions, legal requirements, financial planning and management, risk management, safety management, patients' rights and interests, performance evaluation and management, performance improvement, etc; rehabilitation service standards mainly include the scope of rehabilitation service and the way of rehabilitation service. This guideline is applicable to guide the organizational construction and management of rehabilitation institutions of all levels, traditional Chinese medicine hospitals or rehabilitation departments of general hospitals in China, with good clinical applicability and effectiveness.